Promoting diagnostic accuracy in the GP management of otitis media in children: findings from a multimodal, interactive workshop on tympanometry and pneumatic otoscopy - Rosenkranz, Sara K.; Abbott, Penelope; Reath, Jennifer; Gunasekera, Hasantha; Hu, Wendy (My University, 2012)
PURPOSE: Previous research has shown that General Practitioners (GPs) rarely use pneumatic otoscopy (PO) or tympanometry (TYM) as recommended by best practice guidelines for diagnosing otitis media (OM). The purpose of this study was to determine whether a multimodal, interactive training workshop on the techniques of PO and TYM would improve the confidence of GPs for diagnosis of otitis media with effusion (OME) and acute otitis media (AOM), and for using PO and TYM. Additionally, we sought to determine whether this training could change GPs’ intentions for using PO and TYM in their practices. METHODS: Twenty-three GPs participated in a three-hour training workshop led by an ENT surgeon, a Paediatrician, and an Audiologist. Prior to and following the workshop, GPs completed questionnaires indicating their previous use and beliefs about the usefulness of PO and TYM, confidence for diagnosing AOM and OME, confidence for using PO and TYM, and intention to use PO and TYM in the future. RESULTS: There were no differences (p > 0.05) from pre- to post-workshop in GP confidence for diagnosing AOM. There were increases in GP confidence for diagnosis of OME (pre: 4.5 ± 0.9, post: 4.9 ± 0.4, p <0.01) and confidence for using PO (pre: 3.6 ± 1.6, post: 4.8 ± 1.0, p <0.01) and TYM (pre: 3.3 ± 1.5, post: 5.0 ± 0.7, p < 0.01), but no change (p >0.05) in intention to use PO or TYM in their practices in the future. CONCLUSION: These results suggest that a multimodal, interactive workshop can significantly increase the confidence of GPs for diagnosis of OME and also for using PO and TYM. It is likely, however, that GPs will need follow-up and further practice with these techniques to implement them in their practices.
Promoting diagnostic accuracy in general practitioner management of otitis media in children: findings from a multimodal, interactive workshop on tympanometry and pneumatic otoscopy
Keywords: Otitis media; Continuing medical education; General practice; Evidence based medicine; Clinical competence